Evaluation of 25-Hydroxyvitamin D Levels in Central Anatolia, Turkey. (25th June 2018) - Solak, Ibrahim; Cihan, Fatma Goksin; Mercan, Seher; Kethuda, Tugba; Eryılmaz, Mehmet Ali
Abstract : Background/Aim . The aim of this study is to evaluate serum 25-hydroxyvitamin D levels measured within one year at an Education and Research Hospital in Turkey to identify vitamin D insufficiency/deficiency (which is very commonly seen in the society) and to provide a current approach to treatment management. Materials and Methods . This retrospective descriptive study was carried out by examining the data relating to 35, 667 individuals. Results . Of the individuals participating in the study, 94.47% had a serum 25-hydroxyvitamin D level less than 30 ng/ml, 76.25% had a serum 25-hydroxyvitamin D level less than 20 ng/ml, and 32.20% had a serum 25-hydroxyvitamin D level less than 10 ng/ml. The mean serum 25-hydroxyvitamin D level of all individuals included in the study was 15.2±8.8 ng/ml. The mean serum 25-hydroxyvitamin D level was 14.5±8.8 ng/ml among women and 18.1±8.4 ng/ml among men, respectively (p<0.001). Conclusion . Vitamin D deficiency/insufficiency is widespread in the world and in Turkey. The data obtained from this study suggest that without measuring serum 25-hydroxyvitamin D level will be cost-effective in every age group (except for those are at risk of toxicity) as in children aged 0-1 year old in Turkey and that making a decision in this direction will make a great contribution to the economy of the country.